Decision Support System For Scholarship Recipients WithPre-tasi CORPORATE SOCIAL RESPONBILITY(CSR) At BINA INSAN UNIVERSITY Usingn Methods (SMART) - milenia, aprilsa; Hardoyo; Pajar Ginanjar Wisnu; efrico, Efrico Fernando Baharsyah; rizki, Riski Ulandari; jimmy, Jimmy Alga; elma, elmayati (Adpebi Science Series, 2022)
Abstract Currently, UNIVERSITY BINA INSAN Lubuklinggau no longer offers online screening tools that allow students to apply for CORPORATE SOCIAL RESPONSIBILITY (CSR) scholarships publicly. The decision-making procedure for scholarship recipient students at BINA INSAN UNIVERSITY is online. rulers and documentaries about books related to the title. The effect of this research is the selection tool for the BINA INSAN UNIVERSITY Social Obligation (CSR) scholarship. This optional tutorial widget is transformed into a personal home page programming language that integrates with MYSQL as the preferred tutorial engine database and integrated business intelligence tool interface. web-based. It can be concluded that the selection of utility helpers is a fixed factor, a fixed factor, a practical additive that can connect and interact with each other to achieve the desired goal . Keywords Decision Support System, Simple Multi-Attribute Rating Technique(SMART),Scholarship CSR,Analysis